Composição da comunidade de macroinvertebrados bentônicos em um rio intermitente do semiárido brasileiro - Medeiros, Fabrícia Maísa de (2017)
In intermittent streams the water flow, along with associated environmental resources, leads to a spatial distribution of macroinvertebrate assemblages, which can assume a high spatio- temporal pattern. The present study aims to describe the spatio-temporal variation in the com- position of benthic macroinvertebrates, associated with environmental factors at the longit u- dinal gradient of the Seridó River. Samples were carried out in three reaches along the Seridó River during the rainy (April and July) and dry (October and January) seasons of 2007 and 2008. At each reach were measured, in situ, environmental variables related to physical and chemical water variables, reach morphometry, substrate composition and habitat structure. Benthic macroinvertebrates were randomly sampled using a "D" shaped net (40 cm wide and 250 μm mesh). A total of 39042 individuals were registered, distributed along 27 taxonomic groups, among which Thiaridae and Chironomidae larvae showed higher densities and oc- curred in all sampling occasions. The ANOVA identified significant differences only between Catureré and Riacho da Serra sites, through Tukey's post hoc test (p = 0.009). Hierarchical Multiple Regression (HMR) showed that only morphometric variables explained variation in macroinvertebrate richness (Fchange = 4.52, g.l. = 4.7, p = 0.04). Segregation was not verified in fauna composition between sites and sampling periods. High density of Thiaridae and Chi- ronomidae larvae may bias the analyzes, leading to a homogenization of the biota. This study suggests a strong influence of dominant taxa, notably exotic specie, on macroinvertebrate structure communities in stream studied.